The Role of Village Enterprises In Improving Community Economic Empowerment in Ngadipiro Village, Nganjuk District - Regita, Dilla; Ayu Paramitha, Dyah (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this research is to examine how BUMDes are contributing to greater economic empowerment in Ngadipiro Village, Nganjuk Regency. Design/Methode/Approach : This research used descriptive qualitative methodology to collect primary and secondary data through documentation, interviews and observation.. Research Finding : The results showed that BUMDes in Ngadipiro Village has been successful in promoting economic improvement through two main programmes, namely a savings and loan scheme that facilitates access to capital for small business actors, and a waste bank that provides economic benefits through waste management and recycling. Both programmes are successful thanks to the active participation of the community in planning, implementation and monitoring, which ensures the sustainability and effectiveness of the programmes. The resulting positive impacts are seen in increased community income and the creation of new economic opportunities, which together contribute to sustainable improvements in village welfare.